2018
DOI: 10.1080/10872981.2018.1435114
|View full text |Cite
|
Sign up to set email alerts
|

Social support in the workplace for physicians in specialization training

Abstract: When becoming a specialist, learning-through-service plays a significant role. The workplace affords good opportunities for learning, but the service-learning period may also impose stress on phycisians in specialization training. In medical work, social support has proved to be a very important factor in managing stress. Social support may afford advantages also for learning and professional identity building. However, little was known about how social support is perceived by doctors in specialization trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 52 publications
1
47
0
3
Order By: Relevance
“…This suggests that social support received from colleagues and supervisors may be an important component for the promotion of this competence. This is in line with previous research (Mikkola et al, ) which has reported that social support at work among physicians can act as an important problem‐solving tool (because it includes sharing knowledge, experiences, opinions, and practical tips), resulting in reduced work stress and increased learning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that social support received from colleagues and supervisors may be an important component for the promotion of this competence. This is in line with previous research (Mikkola et al, ) which has reported that social support at work among physicians can act as an important problem‐solving tool (because it includes sharing knowledge, experiences, opinions, and practical tips), resulting in reduced work stress and increased learning.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, because high‐strain jobs (Holman & Wall, ; Taris & Feij, ) and a lack of social support (La Fleur & Salthouse, ) can hamper learning and learning‐related outcomes, it is possible that working in high‐strain and high‐strain isolated jobs could prevent the acquisition of cross‐cultural competence. On the other hand, active jobs (Hausser et al, ; Taris & Kompier, ) and social support (Mikkola, Suutala, & Parviainen, ) are likely to facilitate and promote work‐related learning, thus active and active collective jobs could be positively associated with cross‐cultural competence.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that when working with children who have chronic or acute conditions within a paediatric unit, managing the stressful environment may be complex for nurses and physicians alike given the age of the patient. Namely, nurses and physicians encounter similar job properties, including direct and indirect exposure to the medical and psychological consequences of severe illness, accidental death and injury, life‐threatening events and child and family distress (Al‐Youbi & Jan, ; López Franco et al, ; Robins Meltzer, & Zelikovsky, ; Taubman–Ben‐Ari & Weintroub, ), alongside excessive workload and limited possibilities to control it (Mikkola, Suutala, & Parviainen, ). These work conditions, in turn, may deplete their resources and lead to exhaustion, which might increase the likelihood of developing specific negative consequences like STS.…”
Section: Discussionmentioning
confidence: 99%
“…direct exposure to the medical and psychological consequences of severe illness, accidental death and injury, life-threatening events and child and family distress (Al-Youbi & Jan, 2013; López Franco et al, 2005; Robins Meltzer, & Zelikovsky, 2009; Taubman-Ben-Ari & Weintroub, 2008), alongside excessive workload and limited possibilities to control it(Mikkola, Suutala, & Parviainen, 2018). These work conditions, in turn, may deplete their resources and lead to exhaustion, which might increase the likelihood of developing specific negative consequences like STS.…”
mentioning
confidence: 99%
“…However, the atmosphere of the clinic, how should I put it, is, so to say, challenging. (R10) Social support from both leaders and co-workers is an important aspect of medical work, since it promotes physicians' well-being and stress management; it also provides many other advantages, such as job satisfaction and commitment (see Mikkola, Suutala and Parviainen, 2018). One option to increase peer support during specialisation would be a system whereby the residents would work in pairs, at least in some phases of workplace learning.…”
Section: Suggestion 1: Encourage the Development Of Professional Compmentioning
confidence: 99%